What is the Success of High School it Education? An Investigation into Higher Education Students’ Knowledge of Spreadsheet Applications - Bakó, Mária; Gergely, Ráthonyi (Applied Studies in Agribusiness and Commerce, 2018)
Teaching Computer Science in higher education is imperative, even though today’s students have been born into a world where technology is an essential part of everyday life. To efficiently master modern, business, technical and scientific knowledge and to proficiently produce quality results in a work environment it is crucial to have high level IT knowledge. In business, Excel is the lingua franca and so knowing how to aptly use spreadsheets is a must for our students. The primary objective of the authors was to examine the perceived and actual knowledge of spreadsheet applications of students entering higher education. Accordingly, a questionnaire and a practical assignment have been developed. In the questionnaire, students were asked to provide information concerning their previous IT studies and rate their knowledge of word processing, spreadsheets and database management. During the practical, students were asked to solve an Excel exercise taken from a high school Computer Science final exam at standard level. Out of the 666 registered students on our electronic education system (Neptun) at the beginning of the year, 557 took part in this survey, and following data cleansing and processing, 513 were considered in the results. Looking at the results of the practical, the most significant proportion of students, 142 of them have performed between 0-10%. A total of 260 students have achieved less than 20% performance and 434 people, which is nearly 85% of students have accomplished less than 40%. Compared to the results from the self-evaluation questionnaire it is very poignant that the actual scores differ quite significantly (in both directions) from the perceived knowledge of the students.JEL Classification: Q20